"The more you know, the more you realise it is really challenging to do": Tensions and uncertainties in person-centred support for people with long-term conditions. Issue 8 (August 2018) - Entwistle, Vikki A.; Cribb, Alan; Watt, Ian S.; Skea, Zoë C.; Owens, John; Morgan, Heather M.; Christmas, Simon
Highlights: Person-centred practice should respect and enable patients as moral agents (76). This entails balancing values that may be in tension, and working with uncertainties (85). Some value tensions are ethically difficult and some uncertainties are intractable (85). Professional and service development efforts should reflect these challenges (79). Abstract: Objective: To identify and examine tensions and uncertainties in person-centred approaches to self-management support – approaches that take patients seriously as moral agents and orient support to enable them to live (and die) well on their own terms. Methods: Interviews with 26 UK clinicians about working with people with diabetes or Parkinson's disease, conducted within a broader interdisciplinary project on self-management support. The analysis reported here was informed by philosophical reasoning and discussions with stakeholders. Results: Person-centred approaches require clinicians to balance tensions between the many things that can matter in life, and their own and each patient's perspectives on these. Clinicians must ensure that their supportive efforts do not inadvertently disempower people. When attending to someone's particular circumstances and perspectives, they sometimes face intractable uncertainties, including about what is most important to the person and what, realistically, the person can or could do and achieve. The kinds of professional judgement that person-centred working necessitates are not always acknowledged and supported. Conclusion: Practical and ethical tensions are inherent in person-centred support and need to be better understood and addressed. Practice implications: Professional development and service improvement initiatives should recognise these tensions and uncertainties and support clinicians to navigate them well.